ANALISIS FAKTOR YANG MENYEBABKAN MENURUNNYA MINAT BELAJAR MATEMATIKA PADA MATERI PECAHAN SISWA KELAS IV SDN SIBREH - Aminah, Siti; Maulidar, Maulidar; Suryawati, Indah (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The aim of this research is to determine the factors causing low interest in learning mathematics in fractions. The approach used in this research is a qualitative approach.